2007
DOI: 10.1016/j.bpc.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric control model of bone remodelling containing periodical modes

Abstract: To help to understand the modelling process that occurs when a scaffold is implanted it is vital to understand the rather complex bone remodelling process prevalent in native bone.We have formulated a mathematical model that predicts osteoactivity both in scaffolds, as well as in bone in vivo and could set a basis for the more detailed allosteric models. The model is extended towards a bio-cybernetic vision of basic multicellular unit (BMU) action, when some of the regulation loops have been modified to reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…These distinct approaches form the basis of many temporal and spatiotemporal models of bone remodeling (Figure 5, which includes all publications from Tables 1-3 and Supplementary Tables S1-S2 but not all labels are shown because of space constraints). Models that do not explicitly follow either approach (Kroll, 2000;Rattanakul et al, 2003;Martin and Buckland-Wright, 2004;Moroz et al, 2006;Moroz and Wimpenny, 2007;Akchurin et al, 2008;Ji et al, 2012;Proctor and Gartland, 2016;Chaiya and Rattanakul, 2017;Javed et al, 2018;Zhao and Zhang, 2019;Javed et al, 2020;Nutini et al, 2021;Jorg et al, 2022) (Table 4) are not included in Figure 5; however, most of those detailed in Supplementary Table S3 show citation connections for the field's literature.…”
Section: Techniques For Mathematical Modeling Of Bone Remodelingmentioning
confidence: 99%
See 2 more Smart Citations
“…These distinct approaches form the basis of many temporal and spatiotemporal models of bone remodeling (Figure 5, which includes all publications from Tables 1-3 and Supplementary Tables S1-S2 but not all labels are shown because of space constraints). Models that do not explicitly follow either approach (Kroll, 2000;Rattanakul et al, 2003;Martin and Buckland-Wright, 2004;Moroz et al, 2006;Moroz and Wimpenny, 2007;Akchurin et al, 2008;Ji et al, 2012;Proctor and Gartland, 2016;Chaiya and Rattanakul, 2017;Javed et al, 2018;Zhao and Zhang, 2019;Javed et al, 2020;Nutini et al, 2021;Jorg et al, 2022) (Table 4) are not included in Figure 5; however, most of those detailed in Supplementary Table S3 show citation connections for the field's literature.…”
Section: Techniques For Mathematical Modeling Of Bone Remodelingmentioning
confidence: 99%
“…The power law models cannot be easily extended for situations like diseases or treatments when these signals are perturbed outside the conditions used to fit the power law parameters. The lack of direct mechanistic interpretation is a common criticism of the power law approach (Moroz and Wimpenny, 2007).…”
Section: Power Law Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of bone metabolism based on the signal transduction models have been presented using the OC and osteoblasts (OB) [7]. The behavior of OC and OB in a cellular environment is recognized as a basic multicellular unit [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…If this model is coupled with the higher scale (the aforementioned tissue-level model), and with the lower scale (with models of cellular networks that predict how osteoclastic and osteoblastic activities are modulated by metabolic, pharmacological or environmental determinants), it could be possible to predict how alteration in such determinants affects the strength of the skeleton. In a recent interesting example of these cell-level models, it is suggested that Hill mechanisms of allosteric regulation could also be used in this context (Moroz & Wimpenny 2007).…”
Section: Cell Level: Bone Remodellingmentioning
confidence: 99%